The effect of using fresh farmyard manure (animal manure) on the severity of Fusarium verticilioides in soil, root, stem, and kernels as well as lodging and borer incidence of maize plants - Elsayed, Samar S. A.; Sehsah, Mohamed D.; Oueslati, Moufida A.; Ibrahim, Omar M.; Hamden, Salem; Seddek, Nermien H.; Abo-Elmagd, Heba I.; Alkhalifah, Dalal Hussien M.; Sheteiwy, Mohamed S.; AbdElgawad, Hamada; El-Saadony, Mohamed T.; El-Tahan, Amira M. (Frontiers in Plant Science, 2023)
Fusarium verticillioides, an important maize pathogen, produce fumonisins, causes stalk rot and consequentially reduce crop growth and yield. Therefore, herein we aimed to evaluate the potential use of two farmyard soil organic manures, i.e., fresh (5-6 days old) and stored (5-6 months old) organic manure, to manage F. verticillioides infections as well as borer incidence and lodging in maize plants. After 30, 60, and 90 days of sowing, samples of soil, roots, and stems were collected to isolate F. verticillioides. Moreover, we estimated ear and kernel rot induced by F. verticillioides at the final harvest. Fresh organic manure treatment increased infection rates of F. verticillioides in soil, roots, stem and kernels compared to the control treatment. In contrast, stored organic manure plots treatments decrease F. verticillioides frequency. At 90 days after sowing, stored organic manure suppressed the survival of F. verticillioides, which reduced the F. verticillioides incidence percent. These results were similar to the effect of herbicides-and insecticide-treated plots demonstrated, which show a significant decrease in F. verticillioides incidence rates. Mycological analysis on symptomless kernels revealed a higher % of pathogen infection in opened husks variety (Balady) than closed husks variety (SC10). Compared with stored organic manure, the stem borer incidence and lodging percentage were the highest in fresh organic manure plots. Finally, these results demonstrated that storing organic manure within five to six months as farmyard manure led to high-temperature centigrade within organic manure, thereby destroying spores of F. verticillioides, whereas fresh organic manure did not.